1990
DOI: 10.1111/j.1749-6632.1990.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Status and Immune Function in Tuberculosisa

Abstract: Both macro- and micronutrients have been shown to affect resistance to tuberculosis, which is mediated by macrophages activated by T lymphocytes. Others have demonstrated inhibition of mycobacterial replication in macrophage cultures treated with vitamin D or retinoic acid. We examined the influence of dietary zinc and vitamin D on resistance to tuberculosis. Guinea pigs were fed diets containing varying levels of zinc or vitamin D, and infected 6 weeks later by the respiratory route with virulent Mycobacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…This information becomes important in view of increasing evidence that except for the well known effects of vitamin D on bone metabolism and growth, its deficiency may have other adverse effects like increasing susceptibility to tuberculosis and other infectious diseases [23,24,29] dental caries [25] and autoimmune diseases such as diabetes [5]. There is also evidence that symptomatic hypocalcaemia is eliminated within 48 h after birth in babies whose mothers had been supplemented during the last trimester of pregnancy [2].…”
Section: Discussionmentioning
confidence: 96%
“…This information becomes important in view of increasing evidence that except for the well known effects of vitamin D on bone metabolism and growth, its deficiency may have other adverse effects like increasing susceptibility to tuberculosis and other infectious diseases [23,24,29] dental caries [25] and autoimmune diseases such as diabetes [5]. There is also evidence that symptomatic hypocalcaemia is eliminated within 48 h after birth in babies whose mothers had been supplemented during the last trimester of pregnancy [2].…”
Section: Discussionmentioning
confidence: 96%
“…It is known that malnourished individuals vaccinated with Bacille Calmette-Guerin vaccine do not respond normally to skin tests with purified protein derivative, but the mechanisms that decrease host response to vaccination or to tubercular infection are unknown. McMurray et al (61) identified four studies in the early literature (1923 through 1961) in which vitamin A deficiency in humans or animals exacerbated tubercular disease. However, no recent studies, particularly on antibody production, have added to this literature.…”
Section: Vitamin a And Immunitymentioning
confidence: 98%
“…Some of the apparent differences in outcome might·be resolved by exploring the antibody response in animals with more marginal forms of vitamin A deficiency and by use in the future of more reliable estimates of vitamin A status in human studies. (61) have recently VITAMIN A AND IMMUNITY reviewed the literature on micronutrient status and immune function in tuberculosis. MycobacterizlJ11 tuberculosis infection remains a major cause of morbidity and mortality among malnourished children, and reactivation of disease later in life may be related to, or a cause of, poor nutritional status.…”
Section: Vitamin a And Immunitymentioning
confidence: 99%
“…The two important micro nutrients, namely Zinc and Copper play distinctive role in the pathophysiological process of Tuberculosis. [3][4][5] Several studies have been done to study the influence of these individual risk factors on the pathophysiology of tuberculosis. However, very few studies have been done to study the correlation between these risk factors in pulmonary tuberculosis.…”
Section: Introductionmentioning
confidence: 99%